2021
DOI: 10.1097/md.0000000000026632
|View full text |Cite
|
Sign up to set email alerts
|

BCL7B is a potential novel diagnosis and prognosis biomarker for sarcomas using bioinformatics analysis

Abstract: BCL7B plays a potential role in the progression of various cancers, while its role in sarcomas is unknown. We aimed to evaluate BCL7B's diagnostic and prognostic value, and potential BCL7B-related mechanisms in sarcomas based on The Cancer Genome Atlas (TCGA) database. We collected patients with sarcoma from TCGA. Wilcoxon rank sum test was used to compare the expression of BCL7B in sarcoma samples with different clinical-pathologic features. Univariate Cox regression analysis and multivariate Cox regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…In addition, BCL7B is involved in immune regulation. Our previous study found that BCL7B was associated with immune infiltration in sarcoma, which was consistent with this study (Yang et al, 2021). Considering the limited reports of BCL7B gene in different kinds of cancers, a comprehensive analysis of BCL7B gene is necessary to explore effective prognostic biomarkers and immune-related mechanisms in cancers.…”
Section: Introductionsupporting
confidence: 90%
“…In addition, BCL7B is involved in immune regulation. Our previous study found that BCL7B was associated with immune infiltration in sarcoma, which was consistent with this study (Yang et al, 2021). Considering the limited reports of BCL7B gene in different kinds of cancers, a comprehensive analysis of BCL7B gene is necessary to explore effective prognostic biomarkers and immune-related mechanisms in cancers.…”
Section: Introductionsupporting
confidence: 90%